Effect of Intravenous Administration of Atropine-Neostigmine in Prevention of Headache after Spinal Anesthesia in Cesarean Section: A Randomized Clinical Trial - Hamidreza Shetabi; Mitra Jabalameli; Reihanak Talakkoub; Amir Mansuri (Journal of Mazandaran University of Medical Sciences, 2023)
Background and purpose: The most common method of anesthesia in Cesarean section is spinal anesthesia (SA). Post-Dural puncture headache (PDPH) is one of the complications of SA. The aim of this study was to evaluate the effect of intravenous administration of atropine and neostigmine in prevention of PDPH following Cesarean section. Materials and methods: This study was performed in 62 candidates of elective Cesarean section with SA in Isfahan Shahid Beheshti Hospital. Patients were randomly assigned into the two groups (n= 31 per group) using Random Allocation Software. After umbilical cord clamping, experimental group received neostigmine 0.5 mg and atropine 0.5 mg (i.v.), while the control group received 10 ml i.v. infusion of normal saline. The incidence and severity of headache were compared between the two groups in the first 48 hours and followed up for one week. Results: In this study, one patient in experimental group (3.2%) and five patients in control group (16.1%) reported PDPH which can be clinically important (P=0.195). Headache was seen in two patients (1 in each group) at recovery and in four at ward in control group (P=0.11). The mean severity of headache was 5 and 4.2±0.45 in experimental group and control group, respectively (P= 0.18). The interval between spinal anesthesia and first onset of headache was one hour in experimental group and 20.8 ± 11.1 hours in control group (P=0.18). Conclusion: According to the present study, the neostigmine (0.5mg) + atropine (0.5mg) is associated with a non- significant reduction in the incidence of headache and its severity after spinal anesthesia that are clinically important.